2011
DOI: 10.1200/jco.2011.29.15_suppl.10631
|View full text |Cite
|
Sign up to set email alerts
|

Redefining CTCs: Detection of additional circulating tumor cells using an antibody capture cocktail and HER2 FISH.

Abstract: Among the 43 CK+ informative cases, an overall concordance of 93% between CTCs and the primary tumor was observed with regards to HER2 status. Concordance was observed in 18 of 19 cases with positive HER2 status (positive predictive value of 90%) and 22 of 24 cases with negative HER2 status (negative predictive value of 96%). There was no difference between the numbers of CK+ CTCs detected in the 19 patients with HER2+ status compared to the 24 HER2-cases (median 5 and 9 CTCs, respectively, p = 0.37). Discorda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Schmitt et al [33] have reported an RT-PCR based test as AdnaTest BC kit and assessed for transcripts for EpCAM, MUC1, HER-2, correlated to bone marrow cells and to ER status, and did find a confirmed difference in detection rates based on the phenotype of the breast cancer. Bischoff [34] reported at ASCO the development of a specific antibody cocktail in order to very individually target and follow by HER-2-positive CTCs as surveillance; this "stealth" maneuver will be most important in clarifying whether CTCs are from the original tumor and are biologically significance in the setting up of a new viable recurrence [35]. Certainly, this begs the question as to if they are detected, when and at what level of number of cells detected will a patient benefit from cytotoxic treatment or even biologic antibody-driven treatment given the attendant side effects of treatment, including infection risk from myelosuppression, gastrointestinal effects, thromboembolic risk, cardiovascular risk, including hypertension and /or cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Schmitt et al [33] have reported an RT-PCR based test as AdnaTest BC kit and assessed for transcripts for EpCAM, MUC1, HER-2, correlated to bone marrow cells and to ER status, and did find a confirmed difference in detection rates based on the phenotype of the breast cancer. Bischoff [34] reported at ASCO the development of a specific antibody cocktail in order to very individually target and follow by HER-2-positive CTCs as surveillance; this "stealth" maneuver will be most important in clarifying whether CTCs are from the original tumor and are biologically significance in the setting up of a new viable recurrence [35]. Certainly, this begs the question as to if they are detected, when and at what level of number of cells detected will a patient benefit from cytotoxic treatment or even biologic antibody-driven treatment given the attendant side effects of treatment, including infection risk from myelosuppression, gastrointestinal effects, thromboembolic risk, cardiovascular risk, including hypertension and /or cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%